COVID-19 Perceived as A Driver for Home Care Based on Digital Solutions with A Senior-Centered Approach - Marilena IANCULESCU; Adriana ALEXANDRU; Lidia BĂJENARUand Cristian PETRACHE (Communications of International Proceedings, 2022)
The use of digital solutions has been enlarged lately for decreasing the burden put on the medical systems by the aging population, COVID-19 pandemic and the growing demands for proactive and preventive healthcare patient-centered services. The use of such solutions for home care is also sustained by the link with the current and new generation of information and communication technology (ICT) - like the Internet of Things, cloud/fog/edge computing, artificial intelligence, etc. - that are comprised in these applications. In digital healthcare solutions, data is of extreme importance due to its sensitive feature. Therefore, special attention is placed on its management to ensure its accuracy, privacy and security. This paper aims to present the driver aspect of COVID-19 for older people home care, highlighting the improvements brought to health data management, the measures adopted in Romania for recovering from the pandemic as well as the directions for mitigating present and future dysfunctionalities of the healthcare system. This approach is a novelty for Romania.
Keywords: aging population; home care; digital solutions; COVID-19